The The Effect Of Strategic Implementation on Organizational Performance of Saccos In Southwestern Uganda - Agaba, Agaba Moses; Bosco, Turtasingura John; David , Kabagambe Jesse (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2023)
The purpose of the study was to examine the effect of strategy implementation on organizational performance of SACCOS in Uganda Case of Lyamujungu SACCO in Kabale District- Southwestern Uganda. The study employed a case study research design. It involved quantitative and qualitative methods which enabled the study to evaluate the relationship between the study variables at a snap shot. A sample of 140 respondents were selected using simple random sampling and purposive sampling techniques. The quantitative and qualitative data from the respondents was analyzed using SPSS Version 21.0 and thematic analysis respectively. Quantitative results in form of descriptive statistics, correlations and regressions were presented in tables based on the study objectives. The study found out that strategy implementation, has a positive significant relationship with organizational performance (r = .315, P≤.01). According to the study's conclusions, the Lyamujungu SACCO instance illustrates how strategy execution impacts organizational performance. According to the report, Lyamujungu SACCO's board of directors should implement its strategy effectively as staff members and clients carry out their job duties. The organization will be able to accomplish its goals of turning a profit thanks to this